Generational Research on Technology Acceptance and Use: What’s Popular Isn’t Always Right - Sell, Anna; Makkonen, Markus; Walden, Pirkko (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
Generations are a popular tool used by practitioners and researchers to divide consumers into groups that purportedly share values and characteristics due to shared life experiences. In the technology use realm, baby boomers’ attitudes and behaviors are assumed to differ from millennials due to their formative years having been markedly different regarding technology access and exposure. While the idea is intuitively compelling, in this paper, we discuss problems with the concept of generations and the proposed mechanisms behind generational differences. We present findings from a systematic literature review investigating generational assumptions and inferences in technology acceptance and use research, revealing a need for a stronger theoretical grounding of generational assumptions and to evaluate other possible causes for differences.